Different Apples, Same Tree: Visualizing Current Biological and Clinical Insights into CTLA-4 Insufficiency and LRBA and DEF6 Deficiencies - Gámez-Díaz, Laura; Seidel, Markus G. (Frontiers in Pediatrics, 2021)
Cytotoxic T lymphocyte antigen-4 (CTLA-4) is a crucial immune checkpoint that is constitutively expressed in regulatory T (Treg) cells. Following T-cell activation, CTLA-4 is rapidly mobilized from its intracellular vesicle pool to the cell surface to control the availability of co-stimulatory B7 molecules, thereby maintaining immune homeostasis. Heterozygous mutations in CTLA-4 lead to defects in i) CTLA-4 ligand binding, ii) homodimerization, iii) B7-transendocytosis, and iv) CTLA-4 vesicle trafficking, resulting in an inborn error of immunity with predominant autoimmunity. CTLA-4 vesicle trafficking impairment is also observed in patients with lipopolysaccharide-responsive beige-like anchor protein (LRBA) deficiency or the differentially expressed in FDCP6 homolog (DEF6) deficiency, caused by biallelic mutations in LRBA and DEF6, respectively. Therefore, patients with CTLA-4 insufficiency, LRBA deficiency, and—most recently reported—DEF6 deficiency present an overlapping clinical phenotype mainly attributed to a defective suppressive activity of Tregs, as all three diseases reduce overall surface expression of CTLA-4. In this paper, we describe the clinical phenotypes of these immune checkpoint defects, their pathomechanisms, and visually compare them to other immune regulatory disorders (IPEX syndrome, CD27, and CD70 deficiencies) by using the immune deficiency and dysregulation (IDDA version 2.1) “kaleidoscope” score. Patients characteristically present with an increased risk of infections, autoimmune cytopenias, multi-organ autoimmunity, and inflammation, which are often severe and life-threatening. Furthermore, these patients suffer an increased risk of developing malignancies, especially Non-Hodgkin’s lymphoma. Successful treatment options include regular administration of soluble CTLA-4-Ig fusion protein, Treg cell-sparing immunosuppressants like sirolimus or mycophenolate mofetil, and hematopoietic stem cell transplantation. This mini-review highlights...